Architectural and Planning Reorganization of Belarussian Cities’ Industrial Zones: Tendencies and Approaches - Y. B. Morozova (Наука и техника)
The paper reveals new approaches to the solution of the problem concerning restructurization and planning reorganization of industrial zones in the cities of the Republic of Belarus due to social and economical changes that are taking place during the last ten years. The results are based on the research of historical processes on industrial area formation in Belarussian cities and general rules of urban planning development.